GEGURITAN MBELING OF ROHMAT DJOKO PRAKOSA IN KUMPULAN GURITAN NGELUK DUWUNG NGGELUNG GUNUNG - PRADANASARI, URI (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2016)
Geguritan mbeling is one kind of geguritan that is rarely encountered in Javanese literature. Rohmat Djoko Prakosa through a work entitled  Kumpulan Guritan Ngeluk Duwung Nggelung Gunung presents a new thing in geguritan. This is a renewal of elements within geguritan creator in the form of theme, the use of language, and facial expression. The theme of sex is a theme that dominates the geguritan Rohmat Djoko Prakosa. Rohmat Djoko Prakosa also delivers with the use of language that includes sounds, word combinations, shortening of words, proprietary writing, and language combinations. Rohmat Djoko Prakosa also uses facial expression that  represents the contents of geguritan mbeling. The shape of faceis mostly using the symbol of fertility. They are female genitals, male genitals, and triangles. Keywords; geguritan mbeling, renewal, structure